A Mexican State-level Perspective on Covid-19 and its Economic Fallout - Cuesta Aguirre, Juan Pablo (IMF Working Papers; Working Paper, 2020)
Mexico has had one of the highest death tolls from Covid-19 and among the largest declines in output compared to peers. This paper utilizes data on Mexico's thirty-two states to better understand the relationship between health and economic outcomes. For instance, did the states with worse pandemic outcomes suffer more economically? What state-level characteristics impacted health and economic outcomes? Among the findings are: individual traits such as age and certain pre-existing conditions were associated with higher illness and fatality risks. States with higher initial health expenditure and capacity on average had a lower case fatality rate. The economic fallout was widespread well beyond the direct impact of the pandemic. Tourism-heavy states were particularly badly affected, while states with larger exposures to manufacturing exports performed better. These findings support the case for adequate health spending, fiscal lifelines for hard-hit workers and sectors, and further integration into global value chains to bolster economic outcomes and resilience.